Sistem Informasi Akuntansi Berbasis WEB sebagai Transparansi dan Sinkronisasi dalam Pengelolaan BUMDES Kabupaten Karawang - Yanti Yanti; Euis Nurlaelasari (Universitas Muhammadiyah Metro, 2022)
This study aims to build a system in developing a reporting scheme and financial management of BUM Desa. The benefit of implementing the system is that all reports and financial management can be synchronized, starting from the BUM Desa unit manager to the reporting parent in the Karawang district. This system is also designed to provide general information to the public regarding the financial management of BUM Desa. The main target of system design is to minimize the occurrence of fraud in the management of BUM Desa from the district level to the village level, so that transparency and accountability in realizing the government's Good Village Governance can be achieved.